The cultural intelligence and religious orientation and their relationship to the meaning of life in a sample of Al-Aqsa University female students in Khan Yunis Governorate - Samaan, Mohammed Rateb (Journal of Educational and Psychological Sciences, 2020)
The study aimed to identify both cultural intelligence, religious orientation and their relationship to the meaning of life in a sample of Al-Aqsa University female students in Khan Yunis Governorate, and the study sample consisted of (120) female students in the academic year (2019-2020), and used the following tools: a measure of both cultural intelligence, religious orientation, and the meaning of life- prepared by the researcher. The study adopted the descriptive approach, The results of the study showed that: the arithmetic mean of the domain of metacognition (4.08), which is a high level, and the field of cognitive dimension (4.14), which is a high level, and the field of motivational dimension (2.48) It is a low level, and the overall score for the measure of cultural intelligence (3.57), which is a high level. The results of the study also showed that: The arithmetic mean of the field of fundamental religious orientation (4.49), which is high, and the field of apparent religious orientation (4.51), which is high, and the degree The total score for the religious orientation scale (4.50), which is a high level. The results of the study also showed that: The arithmetic mean for the goal area of ​​life (3.91), which is high, for the field of acceptance and satisfaction with life (3.95), which is high, and for the quality of life field (3.63) The results of the study also showed the presence of statistically significant correlation coefficients at level (0.01) between the domains of the scale of religious orientation, the meaning of life, the overall degree of the scale of each religious orientation, and the meaning of life, The study recommended enhancing cultural intelligence in its fields, designing religious counseling programs for female students, emphasizing awareness activities and activities, and strengthening the role of community institutions to work on highlighting the true meaning of life for female students.